TiO2 nanoparticles coated with bio-inspired ligands for the safer-by-design development of photocatalytic paints. Issue 1 (24th December 2020) - Laisney, Jérôme; Rosset, Aurélie; Bartolomei, Vincent; Predoi, Daniela; Truffier-Boutry, Delphine; Artous, Sébastien; Bergé, Virginie; Brochard, Gregory; Michaud-Soret, Isabelle
Abstract : Stabilization and coating with bio-inspired ligands of TiO2 nanoparticles for the development of safer-by-design photocatalytic paints. Abstract : Addition of titanium dioxide nanoparticles (TiO2 NPs) in photocatalytic paints represents a promising alternative aiming to mineralize gaseous pollutants, such as volatile organic compounds (VOCs). However, the risks of release of nanoparticles to human health and the environmental impact have to be taken carefully into account for their development. To take into account these risks, we develop a new method of TiO2 NP synthesis. Here, we report the electrostatic stabilization in aqueous medium with pyrophosphate buffers of different pH ranges followed by coating with bio-inspired molecules (lysine, deferoxamine, dopamine) and polymers (polyacrylic acid, polyethylene glycol, polydopamine) of 4–5 nm spherical photocatalytic TiO2 NPs for the development of safer-by-design photocatalytic paint. Characterization of the so-formed TiO2 nanocomposites by dynamic light scattering (DLS), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) spectroscopy and X-ray photoelectron spectroscopy (XPS) showed the good grafting of the ligands on the TiO2 surface and an enhanced stability in water compared to the pristine TiO2 NPs. The photocatalytic activity of the TiO2 nanocomposites was investigated by following the degradation of methylene blue (MB) under irradiation. The results showed a modulation of the photocatalytic activity (decrease or increase of the MB degradation rate) as a function of the nature/binding strength of the bio-inspired coating on the oxide surface. Finally, the most promising nanocomposites were incorporated in paints on which preliminary chalking assays were performed after storage for one year in the dark or in interior daylight.